Enhanced Drug Delivery to the Skin Using Liposomes. Issue 7 (July 2018) - Blueschke, Gert; Boico, Alina; Negussie, Ayele H.; Yarmolenko, Pavel; Wood, Bradford J.; Spasojevic, Ivan; Fan, Ping; Erdmann, Detlev; Schroeder, Thies; Sauerbier, Michael; Klitzman, Bruce
Abstract : Background: Enhancing drug delivery to the skin has importance in many therapeutic strategies. In particular, the outcome in vascularized composite allotransplantation mainly depends on systemic immunosuppression to prevent and treat episodes of transplant rejection. However, the side effects of systemic immunosuppression may introduce substantial risk to the patient and are weighed against the expected benefits. Successful enhancement of delivery of immunosuppressive agents to the most immunogenic tissues would allow for a reduction in systemic doses, thereby minimizing side effects. Nanoparticle-assisted transport by low temperature–sensitive liposomes (LTSLs) has shown some benefit in anticancer therapy. Our goal was to test whether delivery of a marker agent to the skin could be selectively enhanced. Methods: In an in vivo model, LTSLs containing doxorubicin (dox) as a marker were administered intravenously to rats that were exposed locally to mild hyperthermia. Skin samples of the hyperthermia treated hind limb were compared with skin of the contralateral normothermia hind limb. Tissue content of dox was quantified both via high-performance liquid chromatography and via histology in skin and liver. Results: The concentration of dox in hyperthermia-treated skin was significantly elevated over both normothermic skin and liver. ( P < 0.02). Conclusions: We show here that delivery of therapeutics to the skin can be targeted and enhanced using LTSLs. Targeting drug delivery with this method may reduce the systemic toxicity seen in a systemic free-drug administration. Development of more hydrophilic immunosuppressants in the future would increase the applicability of this system in the treatment of rejection reactions in vascularized composite allotransplantation. The treatment of other skin condition might be another potential application.